Pendampingan Monitoring Revitalisasi di Sekolah Menengah Pertama ‎Negeri 5 Takisung pada Rehab Ruang Administrasi dan Ruang UKS: Pengabdian - Nurjanah; Amelia Rizyan Nyssa; Muya Ryan Hidayat; Intan Safitri; Marlia Adriana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Education Unit Revitalization Program aims to modernize and improve the quality of education across Indonesia through infrastructure enhancement, digitalized learning systems, and capacity building for educators. SMPN 5 Takisung is one of the target schools, with construction activities in the administration and health unit rooms, covering work from foundation to roof. Each project stage carries potential risks that require careful supervision regarding time, cost, and quality. The program involves Planning, Supervisory,Organizer , and Facilitators for guidance, monitoring, and educating the school staff. Implementation includes initial assessment, training and mentoring, and evaluation. The outcome is expected to enhance the school’s understanding and ability to manage development projects effectively.